ANALISIS PEMAKAIAN BETON PRECAST , READY MIX DAN BETON OLAH PADA PROYEK PEMBANGUNAN JALAN TOL - Pardede, Johanson (Menara: Jurnal Teknik Sipil, 2023)
This study aims to determine the method and its effect on the application of the use of ready-mixed concrete, processed concrete and precast concrete in the Cimanggis-Cibitung toll road construction project. Concrete is a structurally strong building material and is widely used in the construction of buildings, roads and dams. Precast concrete is a concrete product for construction that is specially produced with a predetermined size. This material is made from various mixtures of aggregates and cement binders. The method used is the AHP method. The resulting concrete consists of cement, sand, split which is processed with a special formulation carried out by the Batching Plant, to become cast concrete that is ready to use. Quality concrete is ready to be served in the Cimanggis-Cibitung toll road project area Section 1 A or as a material for making precast concrete. The expert opinion of the SKA Muda owner regarding the calculation of suitable concrete for the Cimanggis-Cibitung toll road work is as follows: Precast Concrete (C01), first place with a total value of 0.691, Ready-to-use Concrete (C02), second place with a total value of 0.249 and Processed Concrete (C03), ranked third with a total score of 0.060.